Marriage Traditions in Suruç and its Surroundings - Atmaca, İlhami; Kılıç, Sami (Erciyes Üniversitesi, 2021)
Marriage, which is the second of the transition periods, is a phenomenon that has different aspects in terms of the participation of the couples to be married in social life, the establishment of solidarity and new ties between families, the formation of social and economic requirements, and several cultural and religious practices. As being a transitional period, marriage is considered one of the important turning points in human life. For this reason, marriage takes place around various stages and certain practices. Transferring the practices carried out in line with religious and cultural elements from generation to generation ensures that the marriage process is observed by the individual, family and region by following certain social patterns. This article consists of the description and analysis of the marriage customs performed with various beliefs and practices in Suruç district of Şanlıurfa province. The data obtained through techniques such as participatory, in-depth observation and interview in the fieldwork were written down using the descriptive method and evaluated in terms of the History of Religions. With this article, it is aimed to reveal the marriage practices and cultural elements in Suruç and its surroundings and to contribute to the studies to be done in this field.

Geçiş dönemlerinden ikincisini oluşturan evlilik, evlenecek çiftlerin toplum hayatına katılımı, aileler arasında dayanışma ve yeni bağların tesisi, sosyal ve ekonomik gerekliliklerin oluşumu ile kültürel ve dini birçok uygulamayı bünyesinde barındırması bakımından farklı yönleri bulunan bir olgudur. Geçiş dönemi olması sebebiyle insan hayatındaki önemli dönüm noktalarından birisi kabul edilen evlilik, çeşitli aşamalar ve belli uygulamalar etrafında gerçekleşmektedir. Dini ve kültürel unsurlar doğrultusunda gerçekleştirilen uygulamaların nesilden nesile aktarılması evlilik sürecinin birey, aile ve yöre tarafından belli toplumsal kalıplara riayet edilerek gerçekleşmesini sağlamaktadır. Bu makale, Şanlıurfa ili Suruç ilçesinde çeşitli inanış ve uygulamalarla gerçekleştirilen evlenme adetlerinin tasviri ve tahlilinden oluşmaktadır. Saha çalışmasında katılımlı ve derinlemesine gözlem ve mülakat gibi tekniklerle elde edilen veriler, deskriptif metot kullanılarak yazıya geçirilmiş ve Dinler Tarihi açısından değerlendirilmiştir. Bu makale ile Suruç ve çevresindeki evlilik uygulamalarının ve içerdiği kültürel unsurların ortaya konulması ve bu alanda yapılacak çalışmalara katkı sağlanması amaçlanmıştır.
Suruç ve Çevresinde Evlilik Adetleri